KAJIAN PERKEMBANGAN POLA RUANG FISIK SPASIAL PERMUKIMAN KUMUH DI KAWASAN KARYA MAKMUR, DENPASAR - KADEK TANIA UTAMI PUTRI; PUTU ELLSA SARASSANTIKA; PUTU HARTAWAN; DESAK KADEK PRADNYA KUMALA DEVI (Universitas Mahasaraswati K. Mataram, 2024)
A livable settlement is a target within the Sustainable Development Goals (SDGs), aimed at creating resilient, inclusive, safe, and sustainable cities and communities. The Karya Makmur area in Denpasar is one of the regions facing significant slum settlement issues. This study aims to identify spatial and physical changes in the area over the past 18 years (2006-2023) and uncover the factors driving the development of slum settlements in this region. A qualitative approach was used, combining map overlay analysis (superimposed analysis) with field data validation. Results indicate that Karya Makmur has undergone major transformations in land use patterns, buildings, and circulation, while showing minor changes in settlement characteristics. The densification process driven by urbanization is identified as the primary factor contributing to the rapid growth of slum areas in this region. This research aims to contribute to future efforts in slum area improvement and planning